Komparasi Daya Adsorpsi Silika Dari Abu Sekam Padi dan Ampas Tebu Terhadap Adsorpsi Pb2+ - Hanandayu Widwiastuti; Riska Yudhistia Asworo (State University of Gorontalo, 2022)
Heavy metals are the main pollutants which numbers are increasing . PB is a heavy metal that has high toxicity when it enters the human body. This is indicated by the LD value of 50 Pb which is 500 mg / kg body weight. Based on Government Regulation No. 82 of 2001, the maximum permissible concentration of Pb2 + in waters is 0.03 mg / L. Therefore, the presence of Pb2 + in the waters needs to be controlled so that pollution in the waters can be reduced. The purpose of this study was to determine the silica adsorption capacity of rice husks and sugarcane bagasse against Pb2 + adsorption. In this study the characterization of each adsorbent was carried out to determine the active functional groups in the bonds that occur. The maximum adsorption capacity of Pb (II) in Si-husk is 126 mg / g at 0.6 g of mass of the adsorbent while the maximum adsorption capacity of Pb (II) in Si-sugarcane is 109.69 mg / g at 0.8 g of adsorbent.